2016
DOI: 10.1016/j.biopsych.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

ITI-007 for the Treatment of Schizophrenia: A 4-Week Randomized, Double-Blind, Controlled Trial

Abstract: The mechanistically novel investigational drug ITI-007 was effective for the treatment of schizophrenia and comparable with placebo on safety measures in this trial. Secondary analyses indicated that ITI-007 improved negative and depression symptoms and might have expanded therapeutic efficacy in comparison with current antipsychotic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 233 publications
(107 citation statements)
references
References 23 publications
6
98
0
3
Order By: Relevance
“…The combination of ITI-007's high potency blockade of 5-HT 2A receptors, efficient dopamine modulation, serotonin reuptake inhibition, and indirect enhancement of glutamatergic neurotransmission has been shown to yield antipsychotic efficacy without motor side effects or cardiometabolic safety issues. ITI-007 demonstrated a reduction of positive symptoms in patients with schizophrenia comparable to risperidone, but with significantly lower blood levels of biomarkers indicative of potential metabolic dysfunction (i.e., insulin, glucose, cholesterol and triglycerides) and prolactin [124]. ITI-007 was also associated with lower rates of motor side effects, such as akathisia, and cardiovascular side effects, such as tachycardia, than risperidone.…”
Section: Development Of Antipsychotics For the Treatment Of Schizophrmentioning
confidence: 99%
See 3 more Smart Citations
“…The combination of ITI-007's high potency blockade of 5-HT 2A receptors, efficient dopamine modulation, serotonin reuptake inhibition, and indirect enhancement of glutamatergic neurotransmission has been shown to yield antipsychotic efficacy without motor side effects or cardiometabolic safety issues. ITI-007 demonstrated a reduction of positive symptoms in patients with schizophrenia comparable to risperidone, but with significantly lower blood levels of biomarkers indicative of potential metabolic dysfunction (i.e., insulin, glucose, cholesterol and triglycerides) and prolactin [124]. ITI-007 was also associated with lower rates of motor side effects, such as akathisia, and cardiovascular side effects, such as tachycardia, than risperidone.…”
Section: Development Of Antipsychotics For the Treatment Of Schizophrmentioning
confidence: 99%
“…In addition, ITI-007 possesses minimal binding affinity for 5-HT 2C serotonin receptors (K i = 173 nM) and the H 1 histamine receptors (K i > 1000 nM) [23] implicated in both weight gain and the aberrant metabolic side effects leading to type II diabetes in patients treated with antipsychotic drugs [162, 164, 165]. Results of human clinical trials of ITI-007, to date [124, 125] have not shown significant weight gain in patients with schizophrenia, suggesting that the compound’s unique receptor binding profile is key in alleviating this side effect.…”
Section: Comparison Of Representative Antipsychotics Haloperidol CLmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, at therapeutic doses it increases phosphorylation of the GluN2B subunits of the NMDA receptor, indirectly leading to enhanced glutamatergic transmission in the mesolimbic pathway. 25 Although previous attempts to solely target the glutamatergic system were not as fruitful as expected, there is a wellidentified link between glutamate and dopamine neurotransmission in schizophrenia and the combination of glutamatergic together with antidopaminergic action may prove more effective in practice. A phase II 4-week randomised, double-blind, controlled trial showed both statistically and clinically significant improvement in schizophrenia symptoms compared with placebo and comparable efficacy to risperidone.…”
Section: Current Development and Future Directionsmentioning
confidence: 99%